Images as Politeness Mechanisms: Insights from Visual Communication in Online Interactions - Nwani-Grace Ugwu, PhD, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This study explores how people use imagery to convey politeness and manage social relationships in online interactions. Three research questions guided the study. Kress and Van Leeuwen’s Multimodal Discourse and Locher and Watts’ Relational Work are the theoretical models adopted for the study. Ten Whatsapp conversations containing emojis formed the data for the research. The conversations were purposively selected because of their relevance to the study. Descriptive survey and qualitative method are employed. The findings reveal that emojis play a significant role in enhancing the tone and intent of messages, allowing users to convey politeness and friendliness in digital communication and images interact with linguistic elements to create cohesive messages. The findings of this study inform the development of more effective online communication strategies, improve online relationships, and enhance understanding of the complex dynamics of online interaction. Individuals are charged to use emojis strategically in digital communication to enhance politeness and convey emotional tone. Emojis should also be in different cultural contexts. More studies should be carried out to explore variations in politeness strategies.
Keywords: Politeness; Emojis; Social media; Online interaction; Multimodal discourse